Towards systemic solutions to food waste: Creative destabilisation and escaping food waste lock-in. (May 2022) - Messner, Rudolf; Johnson, Hope; Richards, Carol
Abstract: This paper identifies and evaluates interventions for addressing the structural conditions in food systems that contribute to food waste. Within the food waste literature, an emerging strand of research is focusing on how food waste has structural causes that are embedded within the fundamental characteristics of food supply chains. This paper draws upon empirical research examining the causes of food waste in the Australian horticulture industry as a context from which to advance understandings of how to dismantle mechanisms of waste creation inherent in food systems. Identifying appropriate interventions to alter the dynamics of food waste production is an important part of addressing food waste as a structural issue, yet such interventions are subject to system resistance to transforming the normal operation of incumbent food systems. Guided by socio-technical transitions theory, this paper investigates ways to increase regime pressure to overcome systemic resistance through the frames of "creative regime destabilisation" and "alternative niche support". A theoretical integration of socio-technical transitions with systems thinking provides deeper insights into the transformative potential of diverse interventions through the identification of 'deep leveraging points', proposing a tangible transition agenda for industry, policy and research. Highlights: Systemic food waste solutions are interventions to escape food system 'lock-in' to surplus and waste creation. Systemic solutions represent responsive policy mixes of multiple concerted interventions that change system dynamics. Interventions must have sufficient leverage to destabilise prevailing industry entitlements of waste creation. Government leadership is essential to accept food waste solutions as an indispensable part of any coherent climate strategy.